Washington Black a novel - Edugyan, Esi (London Serpent's Tail, 2018)
When two English brothers take the helm of a Barbados sugar plantation, Washington Black--an eleven-year-old field slave--finds himself selected as personal servant to one of these men. To his surprise, the eccentric Christopher 'Titch' Wilde is a naturalist, explorer, inventor and abolitionist, and he wants Washington to help him create the perfect aerial machine
1
Keywords: Male friendship -- Fiction; Slaves -- Barbados -- 19th century -- Fiction